Selection Criteria, Yield Relationship with Component Traits and Grouping of Tropical Japonica, Indica Lines and Derived Hybrids of Rice (Oryza sativa L.) - Soni, Sandeep Kumar; Yadav, VK; Pratap, N; Bhadana, VP; Ram, T (SAARC Journal of Agriculture, 2014)
Forty-five rice lines comprising of thirty derived hybrid lines obtained from ten tropical Japonica, three Indica and two national checks viz. Pusa Basmati 1121 and Sarjoo-52 were evaluated for selection parameters, yield contributing components and genetic divergence. Fifteen quantitative and three qualitative traits were studied from experimentation with randomized block design during Kharif 2011. The phenotypic coefficient of variability was higher than genotypic coefficient of variability for all of the traits. The highest estimates of broad sense heritability coupled with genetic advance in per cent of mean was recorded for spikelets per panicle, plant height followed by L:B ratio, spikelets per panicle, grains per panicle, biological yield per plant, flag leaf area, days to 50% flowering, plant height which might be due to the additive nature of gene action. Such results indicated that these traits will be reliable for the effective selection. Highly positive and significant correlation was observed at both phenotypic and genotypic level between grain yield per plant and biological yield per plant, followed by panicle bearing tillers per plant, spikelet fertility, panicle length, 1000- grain weight, grains per panicle, panicle weight, flag leaf length, spikelet per panicle, flag leaf area, kernel length, flag leaf width, days to 50% flowering, and harvest index. This relationship reflected that grain yield and aforesaid economic traits can be increased simultaneously in breeding programme to develop high yielding Indica as well as Tropical Japonica rice varieties. Whole genotypes grouped in 8 non-overlapping clusters exhibited maximum genetic diversity between clusters III i.e., TJ- 64897 × NDR-359, TJ-64897 × CSR36, TJ-64897 × PB-1 and VIII i.e., TJ-11010 × NDR359, TJ-11010 × PB-1, TJ-16081 × NDR-359, TJ-16081 × PB-1. These clusters also stand for early days to flowering, short slender, second highest harvest index and panicle bearing tillers per plant, spikelets per panicle, grains per panicle, spikelet fertility, 1000- grain weight, long bold slender, biological yield per plant, and grain yield per plant. These genotypes showing higher mean performance for aforesaid traits can be exploited for enhancing hybrid vigour of desired New Plant Type with higher number of panicle bearing tillers per plant, spikelet per panicle and grains per spike in Indica as well as Tropical Japonica rice varieties for achieving higher yield. DOI: http://dx.doi.org/10.3329/sja.v11i2.18399 SAARC J. Agri., 11(2): 17-32 (2013)